Effects of pesticide dichlorvos on liver injury in rats and related toxicity mechanisms - Pengcheng Zhang; Zixian Zhou; Jiaqi Yao; Yuhong Jiang; Hang Lei; Zhijun Xie; Juan Li; Xianlin Zhao; Lv Zhu; Meihua Wan; Ling Liu; Wenfu Tang (Ecotoxicology and Environmental Safety)
Dichlorvos (DDVP) is an organophosphorus pesticide commonly utilized in agricultural production. Recent epidemiological studies suggest that exposure to DDVP correlates with an increased incidence of liver disease. However, data regarding the hepatotoxicity of DDVP remain limited. Additionally, the regulatory mechanisms underlying DDVP-induced liver injury have not been thoroughly investigated. In this study, we utilized Wistar rats and BRL-3A cells to establish in vivo and in vitro models for examining the effects of DDVP exposure on liver damage. Our findings indicate that DDVP impairs hepatocyte autophagy and increases ROS activity. RNA sequencing and metabolomic analyses revealed that the pathways affected by DDVP exposure in hepatocytes include ABC transporters and amino acid biosynthesis processes. Furthermore, targeting IRGM overexpression through hepatic portal vein injection of adeno-associated virus mitigated DDVP-induced liver injury. These results demonstrate that DDVP exposure induces liver damage in rats through mechanisms that are dependent on ROS and autophagy, at least in part by downregulating IRGM. Our study offers new insights into the molecular mechanisms of liver injury following organophosphate poisoning and suggests that IRGM may represent a novel therapeutic target for DDVP-induced liver injury.